Chronic recurrent multifocal osteomyelitis in a 13 year old female athlete: a case report - Ferguson, Brad (Canadian Chiropractic Association, 2013)
Chronic recurrent mutlifocal osteomyelitis (CRMO) is an extremely rare skeletal disorder in the younger population. It presents with multifocal bony lesions that often mimic more sinister diagnoses such as infection or neoplasm. The cause of this condition remains unknown and there is limited evidence on effective treatments. In this case, a 13-year-old female athlete presented to a sports chiropractic clinic with non-traumatic onset of right ankle pain. After failed conservative management, radiographs and MRI were obtained exhibiting a bony lesion of the distal tibia resembling osteomyelitis. The patient was non-responsive to antibiotics, which lead to the diagnosis of CRMO. CRMO should be considered as a differential diagnosis for chronic bone pain with affinity for the long bones of the lower extremity in children and adolescents. The role of the primary clinician in cases of CRMO is primarily that of recognition and referral for further diagnostic investigations.